INTERPRETASI KARAKTER KUNTHI OLEH TIGA PENARI PADA PERTUNJUKAN WAYANG ORANG SRIWEDARI - Retno Purwanti; Sri Rochana Widyastutieningrum (Institut Seni Indonesia Surakarta, 2015)
This study focuses on the characterization of figure Kunthi in the performance of traditional stage showWayang Orang Sriwedari. The research is based on the assumption that the character of Kunthi representsthe profile of a wise woman who deserves to be emulated by women today. The study describes the interpretationof the character of Kunthi by three dancers in Wayang Orang performances at Sriwedari. The implementationof the role by one performer and another shows a difference. The difference in the implementation of thesethree dancers formulates the problems to be addressed in the study including how the interpretation ofWayang Orang dancers at Sriwedari expresses the character of Kunthi in the story Kunthi Purwa. Theimplementation of the character of Kunthi by Darsi Pudyorini, Nanik Setyorini, and Sri Lestari (WayangOrang performers at Sriwedari) shows differences in the way they express the character of Kunthi.Keywords: character, Kunthi, Wayang Orang Sriwedari